Identity, Familia, and Belonging - Alicia Long; Denice Adkins (The International Journal of Information, Diversity, & Inclusion)
The lack of diversity in the library and information science (LIS) field is a historical problem in a profession that strives to provide access to information for all. Many librarians of Latin American heritage are and have been members and/or leaders of the American Library Association (ALA). Some of them are also members of and participate actively in the National Association to Promote Library & Information Services to Latinos and the Spanish Speaking (REFORMA). The purpose of this case study is to understand how librarians of Latin American heritage (LLAH) experience a sense of belonging within librarianship based on their dual identity as REFORMA and ALA members. Through semi-structured interviews with eight LLAH who are members of and leaders in ALA and REFORMA and analysis of documents from both associations, we identified three main themes. LLAH are a diverse group, intersectional, from different ethnicities and cultural backgrounds with the common goal of serving Latino communities. In REFORMA, these diverse professionals balance their individual and social identities to find a community and a support system that helps the sense of belonging in a predominantly White profession. Findings from this study have implications for professional associations and their leaders who wish to make librarians who are Latine feel that they belong in LIS.